2018
DOI: 10.1098/rspb.2018.1020
|View full text |Cite
|
Sign up to set email alerts
|

Body mass predicts isotope enrichment in herbivorous mammals

Abstract: Carbon isotopic signatures recorded in vertebrate tissues derive from ingested food and thus reflect ecologies and ecosystems. For almost two decades, most carbon isotope-based ecological interpretations of extant and extinct herbivorous mammals have used a single diet–bioapatite enrichment value (14‰). Assuming this single value applies to all herbivorous mammals, from tiny monkeys to giant elephants, it overlooks potential effects of distinct physiological and metabolic processes on carbon fractionation. By … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 43 publications
3
72
1
1
Order By: Relevance
“…I combine published ungulate and primate δ 13 C enamel values from the Omo‐Turkana Basin during A. anamensis' times (4.2–3.9 Ma) and convert those values to δ 13 C diet values based on the body mass‐dependent ε * enamel‐diet values of Tejada‐Lara et al () [Equation (5)]. Since foregut or hindgut fermenting metabolism of fossil taxa is unknown, I use Tejada‐Lara et al's () equation for all organisms combined: ε * = 2.4 + 0.034 (BM), where BM equals body mass. Faith, Rowan, Du, and Koch () recently classified all Omo‐Turkana fossil ungulates utilized here by mammal size class.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…I combine published ungulate and primate δ 13 C enamel values from the Omo‐Turkana Basin during A. anamensis' times (4.2–3.9 Ma) and convert those values to δ 13 C diet values based on the body mass‐dependent ε * enamel‐diet values of Tejada‐Lara et al () [Equation (5)]. Since foregut or hindgut fermenting metabolism of fossil taxa is unknown, I use Tejada‐Lara et al's () equation for all organisms combined: ε * = 2.4 + 0.034 (BM), where BM equals body mass. Faith, Rowan, Du, and Koch () recently classified all Omo‐Turkana fossil ungulates utilized here by mammal size class.…”
Section: Methodsmentioning
confidence: 99%
“…Based on published body size estimates of A. anamensis , I examine if changing the ε * enamel‐diet value from Cerling et al's () +14‰ based on large ruminant and non‐ruminant mammals to a body‐size dependent ε * enamel‐diet value after methods of Tejada‐Lara et al () significantly alters the estimation of A. anamensis' %C 4 diet. I also explore if different vegetation structures may be responsible for potential isotopic equifinality between A. anamensis and “savanna” chimps.…”
Section: Approach Of Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Tejada-Lara et al (2018) suggested that body mass influences physiological carbon enrichment (□* diet-bioapatite ) in mammals, and provided equations to determine these values of enrichment. Carbon isotopic data presented here are from mammals (extinct and extant) with body mass varying from 38 to 6,300 kg (Table 1), □* diet-bioapatite varied between 12.47 to 14.84 ‰, we used four values: +12 ‰ for taxa weighting less than 75 kg; +13 ‰ for taxa weighting between 75 kg to 600 kg; +14 ‰ for taxa weighting between 600 kg to 3,500 kg; and, finally, +15 ‰ for taxa weighting more than 3,500 kg (Table S3).…”
Section: Methodsmentioning
confidence: 99%